Strength of bacterial adhesion on nanostructured surfaces quantified by substrate morphometry. Issue 42 (10th October 2019) - Spengler, Christian; Nolle, Friederike; Mischo, Johannes; Faidt, Thomas; Grandthyll, Samuel; Thewes, Nicolas; Koch, Marcus; Müller, Frank; Bischoff, Markus; Klatt, Michael Andreas; Jacobs, Karin
Abstract : Bacterial adhesion to nanostructured surfaces can be quantified by surface morphometry: the surface area that is accessible in a certain depth for tethering cell wall molecules equals the fraction of adhesion force as compared to a smooth surface. Abstract : Microbial adhesion and the subsequent formation of resilient biofilms at surfaces are decisively influenced by substrate properties, such as the topography. To date, studies that quantitatively link surface topography and bacterial adhesion are scarce, as both are not straightforward to quantify. To fill this gap, surface morphometry combined with single-cell force spectroscopy was performed on surfaces with irregular topographies on the nano-scale. As surfaces, hydrophobized silicon wafers were used that were etched to exhibit surface structures in the same size range as the bacterial cell wall molecules. The surface structures were characterized by a detailed morphometric analysis based on Minkowski functionals revealing both qualitatively similar features and quantitatively different extensions. We find that as the size of the nanostructures increases, the adhesion forces decrease in a way that can be quantified by the area of the surface that is available for the tethering of cell wall molecules. In addition, we observe a bactericidal effect, which is more pronounced on substrates with taller structures but does not influence adhesion. Our results can be used for a targeted development of 3D-structured materials for/against bio-adhesion. Moreover, the morphometric analysis can serve as a future gold standard for characterizing a broad spectrum of material structures.